157 18F-sodium fluoride positron emission tomography, aortic disease activity and ischaemic stroke risk. (4th June 2021) - Fletcher, Alexander; Tzolos, Evangelos; Joshi, Shruti; Kwiecinski, Jacek; Bing, Rong; Syed, Maaz; Doris, Mhairi; van Beek, Edwin; Moss, Alistiar; Walker, Niki; Joshi, Nikhil; Pawade, Tania; et al.
Abstract : Background: Arterial 18F-sodium fluoride (18F-NaF) activity on positron emission tomography (PET) is a marker of active microcalcification and atherosclerosis. Coronary 18F-NaF activity (CMA) predicts coronary artery disease progression and subsequent myocardial infarction. We aimed to investigate whether aortic 18F-NaF activity (AMA) predicts thoracic aortic atherosclerotic disease progression and subsequent ischaemic stroke in patients with established cardiovascular disease. Methods: In a post-hoc observational cohort study, we evaluated AMA in patients with stable coronary artery disease (n=239) or aortic stenosis (n=158) who had underwent thoracic 18F-NaF PET and computed tomography (CT). We assessed the associations between AMA and progression of thoracic aortic calcification on follow up CT and subsequent ischaemic stroke or myocardial infarction. Results: In 141 patients with repeat CT imaging at 12.7±2.7 months, AMA correlated with progression of thoracic aortic calcium scores (r=0.21, p=0.011). In 397 patients, 16 had an ischaemic stroke and 25 had a myocardial infarction after 4.7±1.6 years. After adjusting for clinical risk factors, CMA and calcium scoring, AMA was associated with stroke (hazard ratio, 1.71 [95% confidence interval 1.00-2.90], p=0.048]). AMA was superior to clinical risk and calcium scores in identifying patients with stroke (c-statistic 0.76 versus 0.58 versus 0.63 respectively, p<0.05). Survival analysis demonstrated that AMA was associated with ischaemic stroke (p<0.001) but not myocardial infarction (p=0.45), whereas CMA was associated with myocardial infarction (p<0.001) but not stroke (p=0.39). Conclusions: In patients with established cardiovascular disease, AMA is associated with progression of aortic atherosclerosis and future ischaemic stroke. Arterial 18F-NaF identifies localised areas of atherosclerotic disease activity that relate to regional atherothrombotic events. Conflict of Interest: none to delcare